Analisis Kualitas Pelayanan dan Implementasi Sistem Informasi Manajemen di PT. PLN ( Persero ) Kabupaten Soppeng - Amriadi, Amriadi; Rachmat, Zul (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2025)
This study aims to analyze the quality of services provided through the implementation of the Management Information System (SIM) at PT. PLN (Persero) SoppengRegency. The focus of the research is to evaluate how the implementation of SIM affects operational efficiency, user satisfaction, and the quality of services provided by PT. PLN (Persero) Soppeng Regency to customers. The methods used in this study are surveys and interviews with users and related stakeholders. The results of the study show that the implementation of a good Management Information System (SIM) can increase responsiveness, accuracy, and transparency in services. However, there are some challenges in user training and system integration that still need to be addressed to achieve more optimal results.